2021
DOI: 10.1111/puar.13339
|View full text |Cite
|
Sign up to set email alerts
|

High‐Stakes Administrative Discretion: What Drives Body‐Worn Camera Activations?

Abstract: Administrative discretion can range from benign to troubling, and law enforcement officers possess the power to use physical violence in the discharge of their duties. Body-worn cameras (BWCs) are a workplace surveillance technology intended to monitor officer behavior in the field, but officers exercise discretion over whether or not to activate their cameras. So, what drives officers to activate BWCs? Combining unique survey and administrative data, three competing explanations of BWC activation are compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…BWC activation rates varied widely across individual officers in Anaheim, California, and were higher during violent crimes than during other types of incidents (Lawrence et al, 2019). Another study confirmed that BWC activation rates were largely driven by officer activity levels and job-related functions, above and beyond officers' demographic characteristics or attitudes toward BWCs (Adams et al, 2021). Researchers have also identified a pronounced influence of organizational policy on activation compliance, with more restrictive policies substantially increasing BWC activation in the field (Katz & Huff, in, press).…”
Section: 2mentioning
confidence: 84%
See 2 more Smart Citations
“…BWC activation rates varied widely across individual officers in Anaheim, California, and were higher during violent crimes than during other types of incidents (Lawrence et al, 2019). Another study confirmed that BWC activation rates were largely driven by officer activity levels and job-related functions, above and beyond officers' demographic characteristics or attitudes toward BWCs (Adams et al, 2021). Researchers have also identified a pronounced influence of organizational policy on activation compliance, with more restrictive policies substantially increasing BWC activation in the field (Katz & Huff, in, press).…”
Section: 2mentioning
confidence: 84%
“…It is important to note that many incidents did not involve officers who were assigned to wear a BWC, contributing to the low percentage of incidents involving BWC activation (17.4%), which should not be considered indicative of low activation compliance (activation compliance was approximately 70% for officers assigned to wear BWCs; Katz & Huff, in press). The use of a direct measure of BWC activation should be considered a strength of the current study given prior research finding variation in activation compliance across officers (Adams et al., 2021; Lawrence et al., 2019) and varied impacts of BWCs on police behavior using measures of activation as opposed to assignment (Hedberg et al., 2017; Huff et al., 2020). Whether multiple BWCs were activated during an individual incident is also accounted for to address potential contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potentially fruitful area of research on supervision comes from the body-worn camera literature (Adams et al, 2021 ; see Lum et al, 2019 for a review of body-worn camera research). Arguments for body-worn cameras typically claim that cameras can increase supervision because supervisors can review footage of police officers performing daily duties (Stoughton, 2018 ).…”
Section: Internal Police Oversightmentioning
confidence: 99%
“…The development of this subtype of discretion helps to better analyze and perform it, while simultaneously nuancing the potential positive outcomes of creative uses of discretion for public service provision. Adams, Mourtgos and Mastracci (2021) ask what drives officers to activate body‐worn cameras? Combining survey and administrative data, three competing explanations of body‐worn cameras activation are compared in one department: officer demographics, job function, and attitudes.…”
mentioning
confidence: 99%